Human Capital Accounting: Problem Status and Suggestions - JANSHANLO, Ramzan; BAIDILDINA, Adilya; KOGUT, Oksana; SULTANOVA, Bakyt; AKIMBAEVA, Karylgash (Journal of Advanced Research in Law and Economics, 2019)
The research considers the theoretical content of the category of human capital, its significance for the development of areas of science and practice. The necessity of reflecting human capital in the accounting and reporting system of Kazakhstani organizations has been substantiated. The main problems of recognition of this most important factor of production are identified, and directions for their further solution are defined. The scientific and practical necessity of introducing a new object of accounting and analysis of “human capital” is substantiated. The problems of accounting for human capital and possible solutions are given, the features of the existing models of human capital assessment are considered. Accounting accounts are recommended, typical accounting records and information regarding human capital are considered, which will need to be disclosed in the financial statements. It was noted that there is no analysis of the formation and efficiency of the use of human capital at the corporate level. The article contains information and conclusions that have practical interest for organizations.